PENERAPAN PEMBELAJARAN STRATEGI PEMECAHAN MASALAH SISTEMATIS DAN WANKAT-OREOVOCZ BERBANTUAN METODE EKSPERIMEN DAN DEMONSTRASI UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA PADA MATERI OPTIK DI KELAS VIII SMP NEGERI 11 JAYAPURA TAHUN AJARAN 2016/2017 - Fian Irsada; Auldry F Walukow; Triwiyono Triwiyono (LPPM Politeknik Saint Paul Sorong, 2020)
The purpose of the study was: 1) finding out students’ enhancement in cognitive learning outcomes based on application of learning systematic troubleshooting solution and Wankat-Oreovocz experimental and demonstration method on optical material. 2) finding out the difference of application of learning systematic troubleshooting solution assisted by experimental method by using Wankat-Oreovocz troubleshooting strategy assisted demonstration to students’ cognitive learning outcomes on optical material. 3) finding out the difference of application of learning systematic troubleshooting solution assisted demonstration method by using Wankat-Oreovocz troubleshooting strategy assisted experiment to students’ cognitive learning outcomes on optical material. 4) finding out the interaction between the application of learning systematic troubleshooting solution and Wanket-Oreovocz. Experimental and demonstration methods have unequal effects. The number of students in this research were 70 students who were divided into two classes, namely the application of learning systematic troubleshooting strategy class amounted 34 students and application of Wanket-Oreovocz troubleshooting strategy class amounted to 36 students in terms of application of experimental and demonstration learning methods. Sample was taken by using purposive sampling technique. Research design used in this research was factorial design. Data was analyzed by using Anova technique with SPSS version 16.0 Software. Research results of data analysis in this research used to improve students’ cognitive learning outcomes in terms of application of learning systematic troubleshooting strategy and demonstration method obtained 0.59 which was in moderate “category”, the application of Wanket-Oreovocz troubleshooting strategy and experimental methods obtained 0.56 which was in moderate “category”. Wanket-Oreovocz troubleshooting strategy that obtained 0.61 was also obtanined 0.61. Results hypothesis showed that there is difference in cognitive learning outcomes between the application of learning systematic troubleshooting strategy and Wanket-Oreovcz (sig-value 0.854 > 0,05); there are differences in cognitive learning outcomes between the application of experimental method and demonstration method (sig-value 0.035 < 0.05);and there is no interaction between systematic troubleshooting strategy and Wanket-Oreovcz, which demonstration method was better used than experiment method.